Computer analysis of images and patterns : CAIP 2019 international workshops, ViMaBi and DL-UAV, Salerno, Italy, September 6, 2019 : proceedings /: CAIP 2019 international workshops, ViMaBi and DL-UAV, Salerno, Italy, September 6, 2019 : proceedings. ([2019]) - Unknown
No abstract available